The draft genome assembly of Dermatophagoides pteronyssinus supports identification of novel allergen isoforms in Dermatophagoides species - Randall, Thomas A. (Int Arch Allergy Immunol, 2018)
BACKGROUND: Dermatophagoides pteronyssinus (DP) and Dermatophagoides farinae (DF) are highly similar disease-associated mites with frequently overlapping geographic distributions. A draft genome of DP was assembled to identify candidate allergens in DP homologous to those in DF, investigate allergen isoforms, and facilitate comparisons with related Acari. METHODS: PacBio and Illumina whole genome sequencing was performed on DP. Assembly and reconstruction of the genomes were optimized for isoform identification in a heterogeneous population. Bioinformatic analyses of Acari genomes were peformed. RESULTS: The predicted size of the DP nuclear genome is 52.5 Mb. A predicted protein set of 19,368 proteins was identified, including all 19 currently recognized allergens from this species. Orthologs for 12 allergens established for DF were found. The population of DP mites showed a high level of heterozygosity that allowed the identification of 43 new isoforms for both established and candidate allergens in DP, including a new isoform for the major allergen Der p 23. Reanalyzing the previous DF data assuming heterozygosity, 14 new allergen isoforms could be indentified. Some new isoforms were observed in both species suggesting that these isoforms pre-dated speciation. The high quality of both genomes allowed an examination of synteny which showed many allergen orthologs are physically clustered but with species specific exon/intron structures. Comparative genomic analyses with other Acariformes mites showed that most of the allergen homologs are widely conserved within this Superorder. CONCLUSIONS: Candidate allergens in DP were identified to facilitate future serological studies. While DP and DF are highly similar genetically, species-specific allergen isoforms exist to facilitate molecular differentiation.